2022
DOI: 10.3389/frvir.2022.742509
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Presence and Learning

Abstract: The highly immersive Virtual reality (VR) headset is gaining popularity in multiple application domains. In the context of learning, it has been proposed to be beneficial by increasing presence and attention in noisy and distracting environments, both factors that are considered important for learning. Despite intensified research efforts in recent years, empirical knowledge of experimental research addressing the link between presence and learning in specific environmental contexts is still rather scarce. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 84 publications
0
8
1
Order By: Relevance
“…In the past 20 + years there has been extensive research into virtual reality as a site of learning that can be utilised in both educational and professional contexts. Some suggest that the more immersive something is, the more information trainees retain (Alhalabi, 2016;Krokos, Plaisant and Varshney, 2019) although others suggest the reverse (Ochs and Sonderegger, 2022). Another study suggested that the emotion elicited by…”
Section: Training In Virtual Realitymentioning
confidence: 99%
“…In the past 20 + years there has been extensive research into virtual reality as a site of learning that can be utilised in both educational and professional contexts. Some suggest that the more immersive something is, the more information trainees retain (Alhalabi, 2016;Krokos, Plaisant and Varshney, 2019) although others suggest the reverse (Ochs and Sonderegger, 2022). Another study suggested that the emotion elicited by…”
Section: Training In Virtual Realitymentioning
confidence: 99%
“…The mean age was 23.1 (SD = 1.65). All participants were students in the field of virtual reality, which avoids possible biases related to the first use of virtual reality which can make it difficult for participants to concentrate (Ochs & Sonderegger, 2022).…”
Section: Participantsmentioning
confidence: 99%
“…Sense of presence is a multidimensional concept generally defined as the sense of being in a context displayed by a virtual environment [25]. Several studies have shown that most virtual environments can induce a sense of presence, which could be linked to emotional reactions and learning [26,27]. In fact, some studies have found a bidirectional relationship between emotions and sense of presence in a therapeutic context, showing that a higher sense of presence is associated with higher emotional intensity and vice versa [28].…”
Section: Introductionmentioning
confidence: 99%